Prototype alat monitoring lingkungan sekolah berbasis Raspberry bagi siswa dan guru SMK Negeri 5 Kabupaten Gowa - Yunus Tjandi Yunus Tjandi; Zulhaji Zulhaji (Universitas Negeri Makassar, 2019)
Improper installation and not in accordance with PUIL standards of Monitoring device, will provide a detriment for consumers of electricity. The objectives to be achieved in the Community Partnership Program (PKM) are: (1) to increase the knowledge of Teachers and Students of Gowa 5 Vocational School (partners) to monitor and control the electrical equipment of the School Environment and electrical equipment using Smartphone/Computer, (2) To improve the skills of Teachers and Students of Gowa 5 Vocational School (partners) in making and utilizing the Raspberry-based Monitoring and Control system, (3) improving the skills of Teachers and Students of the National Vocational School and Somba Opu SMKT in making interface and application system based on Arduino Mega to monitor and control electrical equipment device of a house/building. The methods used of this Workshop are the lecture method, discussion, and demonstration. The results of this PKM are (1) Increasing Partner Knowledge in making Arduino Mega-based monitoring and control software, (2) Increasing Partner Skills in terms of making and utilizing Arduino Mega-based Monitoring and Control System for monitoring and controlling electricity devices of a house/building, (3) increasing Skill and knowledge of Partners in order to be able to provide easy solutions at Gowa 5 Vocational School, in monitoring and controlling electrical devices in the School environment, so that the tools can be controlled using smartphone, both from a close range or remotely. The method used in giving the material is the lecture method, and discussion while the application uses the demonstration method. The results of the Community Partnership Program (PKM) illustrate that the group of Teachers and Students of Gowa 5 Vocational School (partners) have: (1) possessed knowledge in making Raspberry-based Monitoring and Control device to monitor School Environments and electrical equipment using Smartphone/Computer, (2) have skills in making and utilizing Raspberry-based Monitoring and Control device, (3) having skills and knowledge to be able to provide easy solutions for Gowa 5 Vocational School.